Composite having radiation shielding function and method for manufacturing the composite having radiation shielding function
A composite material with high radiation shielding powders and a low melting point metal matrix addresses the limitations of conventional materials by offering lightweight, high-strength, and thermally stable radiation shielding solutions for diverse applications.
Patent Information
- Application Number
- JP2024120809
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2044-07-26
AI Technical Summary
Conventional radiation shielding materials are heavy due to the use of metals like lead and tungsten, and composites with boron carbide have low powder content, limiting their application range and stability at high temperatures.
A composite material is developed with a high content of radiation shielding powders such as gadolinium oxide, boron carbide, and barium sulfate, combined with a low melting point metal matrix like aluminum, using a non-powdered silica-based binder and a liquid organic-inorganic sealant to form a porous structure that is impregnated with molten metal, ensuring high thermal stability and radiation shielding efficacy.
The composite material achieves a high radiation shielding effect with a lightweight structure, capable of withstanding high temperatures and providing excellent strength and thermal conductivity, suitable for various applications including building materials and machinery.
Smart Images

Figure 0007606793000007 
Figure 0007606793000008 
Figure 0007606793000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite having a radiation shielding function and a method for manufacturing a composite having a radiation shielding function. In particular, the present invention relates to specific inorganic powders or metal powders having a radiation shielding effect, such as gadolinium oxide (Gd2O3) powder, boron carbide (B4C) powder, boron oxide (B2O3) powder, boron (B) powder, barium sulfate (BaSO4) powder, strontium oxide (SrO) powder, tungsten (W) powder, tungsten oxide (W2O3) powder, tungsten carbide (WC) powder, molybdenum (Mo) powder, molybdenum oxide (MoO3) powder, iron (Fe) powder, iron oxide (Fe2O3) powder, and ferrite powder mainly composed of iron oxide (hereinafter, these will be collectively referred to as "iron oxide powder"). The present invention relates to a composite material obtained by impregnating voids in a porous preform containing at least one selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin, and lead, and a low-melting-point metal or a low-melting-point alloy of the low-melting-point metal and another metal, each having a melting point of 200° C. or more and 900° C. or less, and then solidifying the voids in the preform, or a composite material having a radiation-shielding function obtained by impregnating the preform with a liquid organic / inorganic sealing agent, heat-treating the agent, and solidifying the composite material (hereinafter, these are also simply referred to as a composite material), and a method for producing the composite material. In particular, the present invention relates to a technology that enables the realization of a composite material obtained by compounding the radiation-shielding powders listed above in a state in which decomposition of the radiation-shielding powders is suppressed. [Background technology]
[0002] In the medical field, radiation shielding materials are used in consideration of X-rays and radiation generated by medical devices and medical equipment. In the nuclear industry, materials that shield radiation such as X-rays, gamma rays, and neutron rays are used in containers and devices for handling and storing unused nuclear fuel. Radiation shielding materials are required to have good heat dissipation properties to block radiation and prevent nuclear chain reactions. Metals such as lead (Pb) and tungsten (W) are generally used as radiation shielding materials, but in recent years, radiation shielding materials that are lightweight, have high heat dissipation properties, and have a large radiation shielding effect are being required, especially for structural members that require radiation shielding effects.
[0003] Conventional radiation shielding materials generally use metallic lead or metallic tungsten. However, these materials have a high specific gravity, and structural materials made from these materials are quite heavy, so their range of use is limited. As listed below, in order to create lightweight structures with radiation shielding effect, materials have been proposed that combine B4C powder or BaSO4 powder, which has a low specific gravity and has a radiation shielding effect, with resin or metal. However, there is a problem in that the content of these powders with radiation shielding effect in the structure is low, limiting the range of application.
[0004] Patent Document 1 proposes a method for producing an aluminum radiation shield containing B4C as described below. Specifically, the radiation shield is proposed by producing a compact of a mixed powder consisting of boron carbide (B4C) powder and aluminum powder, sintering the compact at a low sintering temperature of 10 to 50°C by vacuum sintering, HIP, or hot pressing, blending the B4C and aluminum, and then heating, melting, and casting the compact. In this method, the content of B4C in the radiation shield is limited to a range of 0.5 to 5 mass% or less, and if the content exceeds this, the viscosity of the molten metal increases, making casting difficult. Therefore, it has been difficult to produce a radiation shield having a greater radiation shielding effect and a B4C content of more than 5v%.
[0005] Patent Document 2 also discloses that a mixture of boron carbide (B4C) particles and aluminum borate whiskers is molded by adding an inorganic binder, and the molded product is sintered in an argon atmosphere at a high temperature of 1250°C for 4 hours to prepare a preform, and the preform is impregnated with molten aluminum alloy at high pressure to prepare a radiation shielding composite. In this method, boron carbide and ceramic whiskers are mixed, and sintered at a high temperature of 1100 to 1400°C to prepare a preform that can withstand high pressure impregnation with aluminum, and the preform is impregnated with molten aluminum alloy to prepare a composite. This method has the problem that the preform must be made at a high temperature, which makes it expensive, and furthermore, the content of boron carbide can only be 1 to 15 wt%, so the content of boron carbide in the radiation shielding composite could not be increased.
[0006] Patent Document 3 discloses that a solid piece of aluminum alloy that melts at 580°C to 610°C is placed on top of a preform made from a mixture of boron-containing ceramic powder, typically boron carbide (B4C), and metal powder containing aluminum, and the solid piece is heated to an infiltration temperature at which it melts and infiltrated for 1 minute to 24 hours to obtain a composite. According to the study by the present inventors, this method requires a long reaction time because the aluminum alloy is naturally infiltrated (infiltrated) into the preform, and unstable Al4C3 is formed in the air and the preform is not 100% impregnated, so a dense and stable radiation shielding composite could not be obtained.
[0007] Also, Patent Document 4 proposes a method of manufacturing a composite by heating a mixed powder of boron carbide powder and aluminum alloy powder, or a mixed powder compact thereof, to a predetermined temperature and maintaining it, and forging or rolling it under the condition of a semi-molten state. According to the study by the present inventors, this method is unable to manufacture a composite with a large area or a thick wall because it is molded at a high temperature. In addition, this technology has problems in that the radiation shielding powder and the aluminum alloy become non-uniform, and it is unable to manufacture a product with a wall thickness of 10 mm or more, because it forcibly forges in a semi-molten state.
[0008] Patent Document 5 proposes a container material in which boron fibers are combined with an aluminum alloy base containing boron. However, the boron fiber content is still low, and boron fibers are expensive, so the range of use is limited. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2002-20828 A [Patent Document 2] JP 2003-121590 A [Patent Document 3] Patent No. 4426293 [Patent Document 4] Japanese Patent Application Publication No. 60-096746 [Patent Document 5] Japanese Patent Application Publication No. 10-319183 Summary of the Invention [Problem to be solved by the invention]
[0010] As mentioned above, in the radiation shielding materials of the prior art, when metallic lead or metallic tungsten is used as the radiation shielding powder, the weight becomes large, or when powders such as boron carbide (B4C) or barium sulfate (BaSO4) are used, the content of the powder having a radiation shielding effect is low in any composite, and a high content could not be realized. In addition, as a prior art, a material in which a radiation shielding powder is mixed with gypsum, rubber, or resin has been proposed. However, in the case of a material using rubber as a matrix, it is difficult to use it for a long time at 200°C or more because it is an organic matter. In addition, in the case of a material using gypsum as a matrix, there is a problem that a dehydration reaction of gypsum occurs when it is used for a long time at a temperature of 100°C or more, and it is not possible to use it for a long time at high temperatures.
[0011] In view of the above-mentioned state of the prior art, the present inventors considered that if a method could be developed to control the content of materials (raw materials) with a high content of radiation shielding powders such as B4C powder, BaSO4 powder, or other gadolinium oxide, strontium oxide, iron oxide, etc., from low to high, and to prepare materials that can be used at high temperatures, the range of radiation shielding applications as structural members (structures) and parts of radiation-related machines would be significantly expanded. In addition, even if radiation shielding powders such as tungsten powder and molybdenum powder, which have a specific gravity of 10 or more, are combined with other materials at a content level that allows stable radiation shielding effect to be exerted, and a lightweight material can be obtained as a composite, they could be used depending on the application, and the range of use would be significantly expanded.
[0012] The present inventors recognized that, in view of the current state of the prior art, a composite material having the following characteristics is desired as a highly practical radiation shielding function composite material. That is, the inventors recognized that a composite material having high strength and a high content of radiation shielding powder, particularly a content of 3v% or more, preferably 60v% or more, and more preferably up to 85v%, a wall thickness of 5mm or more, preferably 10mm or more, a high radiation shielding effect, lightweight, and usable for large structures, a building wall material, a machine protective structure, and further a composite material of a low melting point metal selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin, and lead, or a low melting point alloy of the low melting point metal and other metals (hereinafter, these may be referred to as "aluminum, etc."), all of which have high thermal conductivity, is desired. It is possible to use low melting point metals other than zinc, tin, and lead as long as they do not impair the object of the present invention. In this specification, volume % is also expressed as "v%" and mass % is also expressed as "w%".
[0013] Therefore, an object of the present invention is to develop a composite having a novel configuration that contains a high content of a powder having a radiation shielding function (radiation shielding powder) and has a high radiation shielding effect. Another object of the present invention is to develop a variety of composites in which the radiation shielding powder content is controlled from a low content of, for example, 3v% to 85v% to a high content according to the application, and that has a degree of strength required for structures such as parts and members that constitute buildings or machines. A further object of the present invention is to develop a new technology that can provide an excellent composite with a radiation shielding powder, which is a composite with an aluminum metal powder, an aluminum alloy powder, or a ceramic powder that has heat resistance and high thermal conductivity and has a molten aluminum metal or aluminum alloy as a matrix. [Means for solving the problem]
[0014] The above object can be achieved by the present invention, which provides a composite having a radiation shielding function as described below. [1] A composite having a radiation-shielding function, comprising a powder having a radiation-shielding effect, the powder being composited in a total amount of 3% by volume or more and 85% by volume or less, A porous composition which is a formed and fired product of a mixture containing one or more types of powder having a radiation shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron powder, boron oxide powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide, and a silica-based binder that is not in powder form. The voids in the molded body (preform) are all impregnated and filled with at least one of a molten low-melting point metal selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin and lead, which has a melting point of 200°C or more and 900°C or less, or a low-melting point alloy of said low-melting point metal and another metal, and then solidified to form a composite, or at least 25 volume % or more of the voids in the porous molded body (preform) are impregnated with a liquid organic / inorganic sealing agent, which is then solidified to form a composite, and A composite having a radiation-shielding function, characterized in that the non-powdered silica-based binder has properties that enable the molding and sintering product to be formed into a porous molded body (preform) at a temperature at which the radiation-shielding powder is not decomposed.
[0015] Preferred embodiments of the above-mentioned complex having a radiation shielding function are as follows. [2] The composite having a radiation-shielding function according to the above item [1], wherein the non-powdered silica-based binder is at least one liquid silica-based binder selected from the group consisting of water glass (sodium silicate), colloidal silica, liquid silicone resin, a silicone resin solution obtained by dissolving a silicone resin in an organic solvent, and a silica alkoxide made of silica and an organic substance and cured by heating at a temperature of 900°C or less, and the mixture is obtained by adding 0.5 to 10 parts by mass of the liquid silica-based binder in terms of SiO2 to 100 parts by mass of the radiation-shielding powder.
[0016] [3] The composite having a radiation-shielding function according to the above item [1] or [2], wherein the liquid organic / inorganic pore-sealing agent is present in the pores of the porous molded body (preform) as a solidified product of the organic / inorganic pore-sealing agent and / or a heat-treated product of the organic / inorganic pore-sealing agent, and the solidified product of the organic / inorganic pore-sealing agent and / or the heat-treated product of the organic / inorganic pore-sealing agent occupies 25% by volume or more of the 100% by volume of the pores of the porous molded body (preform) before impregnation, and when the entire preform after impregnation is taken as 100% by volume, the solidified product of the organic / inorganic pore-sealing agent and / or the heat-treated product of the organic / inorganic pore-sealing agent occupies 5% by volume or more.
[0017] [4] The liquid organic / inorganic sealing agent has a low viscosity of 50 mPa·s or less and contains 30 mass% or more of non-volatile components. A liquid methyl silicate compound which is methyl silicate Si(OCH3)4 or a dimer or tetramer oligomer obtained by partially hydrolyzing the methyl silicate, and which is adjusted so that the non-volatile component is 30 mass% or more; A liquid ethylsilicate compound which is ethylsilicate Si(OC2H5)4 or a dimer or tetramer oligomer obtained by partially hydrolyzing the ethylsilicate, and which is adjusted so that the non-volatile component is 30 mass% or more; A silicone resin or its derivative having a siloxane bond and adjusted so that the non-volatile component is 30% by mass or more. The complex having a radiation-shielding function according to any one of the above [1] to [3], which is at least one selected from the group consisting of liquid alkoxysilane compounds which are alkoxysilane derivatives and react with moisture in the air to undergo a condensation reaction to generate silicone-oxygen organic compounds (Si-OR).
[0018] As another embodiment, the present invention provides the following method for producing a composite having a radiation shielding function. [5] A method for producing a composite having a radiation-shielding function, comprising: a matrix of at least one of a molten low-melting-point metal selected from the group consisting of aluminum metal, an aluminum alloy, zinc, tin, and lead, or a low-melting-point alloy of said low-melting-point metal and another metal; and a powder having a radiation-shielding effect in a total amount of 3 volume % or more and 85 volume % or less, the method comprising the steps of: a step of adding a non-powdered silica-based binder to one or more types of powder having a radiation shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron oxide powder, boron powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide, to form a mixture, and then firing the resulting molded body at a temperature of 300° C. or higher and 900° C. or lower to produce a porous molded body (preform); a molten metal of at least one low-melting-point metal selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin and lead, which has a melting point of 200°C to 900°C, and which is melted at a temperature of 300°C to 900°C, or a low-melting-point alloy of said low-melting-point metal and other metals, is cast into the porous molded body (preform) obtained in the above step, and the molten metal is held at a high pressure of 20 MPa to 200 MPa for 3 to 15 minutes in order to impregnate the porous molded body (preform) with the molten metal, and then the composite impregnated with the molten metal is removed within 15 minutes and cooled, thereby suppressing decomposition of the radiation-shielding powder in the composite.
[0019] [6] A method for producing a composite having a radiation-shielding function, comprising preparing a composite containing a powder having a radiation-shielding effect in a total amount of 3 volume % or more and 85 volume % or less, the powder being composited, the method comprising the steps of: a step of adding a non-powdered silica-based binder to one or more types of powder having a radiation shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron oxide powder, boron powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide, to form a mixture, and then firing the obtained molded body at a temperature of 300° C. or more and 900° C. or less to prepare a porous molded body (preform); and a compounding step of: impregnating, in a vacuum, a liquid organic / inorganic sealing agent having a viscosity of 50 mPa s or less and containing 30% by mass or more of non-volatile components into voids of the porous molded body (preform) obtained in the step of producing the porous molded body (preform), or impregnating the voids at a pressure of 10 atmospheres or less by applying pressure after the vacuum impregnation, and then heating the voids to a temperature of 200°C or more and 900°C or less, so that a solidified product of the liquid organic / inorganic sealing agent and / or a heat-treated product of the liquid organic / inorganic sealing agent remains in an amount of 25% by volume or more relative to 100% by volume of the voids of the porous molded body (preform), thereby compounding the radiation-shielding powder with a component derived from the liquid organic / inorganic sealing agent.
[0020] A preferred embodiment of the method for producing a composite having a radiation-shielding function described above in [5] or [6] is as follows. [7] The liquid organic / inorganic sealing agent has a low viscosity of 50 mPa s or less and contains 30 mass % or more of non-volatile components. A liquid methyl silicate compound which is methyl silicate Si(OCH3)4 or a dimer or tetramer oligomer obtained by partially hydrolyzing the methyl silicate, and which is adjusted so that the non-volatile component is 30 mass% or more; A liquid ethylsilicate compound which is ethylsilicate Si(OC2H5)4 or a dimer or tetramer oligomer obtained by partially hydrolyzing the ethylsilicate, and which is adjusted so that the non-volatile component is 30 mass% or more; A silicone resin or its derivative having a siloxane bond and adjusted so that the non-volatile component is 30% by mass or more. The method for producing the composite having radiation shielding function described in [6] above, wherein the alkoxysilane derivative is at least one selected from the group consisting of liquid alkoxysilane compounds that react with moisture in the air to undergo a condensation reaction to produce silicone-oxygen-organic compounds (Si-OR).
[0021] [8] The method for producing a composite having a radiation-shielding function according to any one of the above [5] to [7], wherein the non-powdered silica-based binder is at least one liquid silica-based binder selected from the group consisting of water glass (sodium silicate), colloidal silica, liquid silicone resin, a silicone resin solution obtained by dissolving a silicone resin in an organic solvent, and a silica alkoxide made of silica and an organic substance and heated and cured at a temperature of 900°C or less, and the mixture is obtained by adding 0.5 to 10 parts by mass of the liquid silica-based binder in terms of SiO2 to 100 parts by mass of the radiation-shielding powder.
[0022] [9] The method for producing a composite having a radiation-shielding function according to the above item [5] or [8], further comprising the step of adding aluminum powder, aluminum alloy powder, or ceramic powder to the radiation-shielding powder in such a manner that, when the total of the aluminum metal powder, aluminum alloy powder, or ceramic powder, and the radiation-shielding powder is taken as 100 mass%, 0.5 to 10 mass% of the non-powdered silica-based binder is added in terms of SiO2 to produce a porous molded body (preform). Effect of the Invention
[0023] Conventionally, structures containing radiation-shielding powders have generally been manufactured as composites by mixing the radiation-shielding powder with aluminum, rubber, or resin. In contrast, according to the present invention, a composite having a radiation-shielding function, which is configured by impregnating all of the voids of the molded body (preform) with a molten metal such as aluminum and solidifying to form a composite, and which has a similar configuration in that it is made using a molded body (preform) containing radiation-shielding powder whose filling rate is controlled from low to high, or a composite having a radiation-shielding function, which is configured by impregnating at least 25% by volume of the voids of the molded body (preform) with a liquid organic / inorganic sealing agent and solidifying to form a composite, is stably provided. In addition, by applying each of the manufacturing methods of the present invention according to the intended use of the composite and skillfully utilizing the above-mentioned two types of configuration, it is possible to stably obtain various composites having high practical value and suitable for desired characteristics, for example, in which the filling rate of the radiation-shielding powder is controlled from low to high and the filling rate is excellent and the strength is suitable for the purpose. The technical features of the present invention are as follows.
[0024] The first feature of the present invention is that one or more types of radiation-shielding powders appropriately selected from a group of radiation-shielding powders having different functionality and characteristics, including gadolinium oxide (Gd2O3) powder, boron carbide (B4C) powder, boron oxide (B2O3) powder, boron (B) powder, barium sulfate (BaSO4) powder, strontium oxide (SrO) powder, tungsten (W) powder, tungsten oxide (W2O3) powder, tungsten carbide (WC) powder, molybdenum (Mo) powder, molybdenum oxide (MoO3) powder, iron (Fe) powder, iron oxide (Fe2O3) powder, and ferrite powder mainly composed of iron oxide, can be used according to the purpose of use, etc. In other words, according to the present invention, it is possible to provide a variety of radiation-shielding composites composed of a single radiation-shielding powder or various combinations of radiation-shielding powders.
[0025] Among the radiation-shielding powders constituting the composite of the present invention, for example, boron carbide containing boron has a radiation shielding effect against neutron rays, tungsten or tungsten carbide has a radiation shielding effect against gamma rays and X-rays, and barium sulfate containing barium has a radiation shielding effect against X-rays and gamma rays. In contrast, according to the present invention, it is possible to provide composites of various configurations with different radiation shielding functions, as listed below. That is, it is possible to provide not only composites obtained by impregnating each powder of the specific radiation-shielding powder group specified in the present invention with a molten metal or liquid organic / inorganic sealing agent such as aluminum and solidifying the powder, but also composites obtained by impregnating two types of radiation-shielding powders, boron carbide and tungsten, and boron carbide and barium sulfate, or three types of radiation-shielding powders, boron carbide and tungsten, and barium sulfate as necessary, with a molten metal or liquid organic / inorganic sealing agent such as aluminum and solidifying the powder. As described above, according to the present invention, by appropriately selecting the radiation-shielding powder defined in the present invention, it is possible to provide a composite that can simultaneously shield against X-rays, gamma rays, and neutron rays.
[0026] A second feature of the present invention is that it is possible to provide a composite having a radiation-shielding function in which the volume fraction of the radiation-shielding powder can be freely controlled from 3v% to 85v%, for example, by adjusting the particle size and blending ratio of the various radiation-shielding powders listed above, and by adding aluminum powder or aluminum alloy powder as necessary. According to the present invention, it is possible to manufacture a structure made of a composite having a radiation-shielding function that realizes a packing fraction (volume fraction) of the radiation-shielding powder of 50v% or more, which is required for a particularly high shielding effect.
[0027] The third feature of the present invention is that the composite having a radiation-shielding function provided by the present invention can be made into the following two different configurations. First, in either configuration, a porous molded body (preform) is used, which is a molded and fired product of a mixture containing one or more types of radiation-shielding powder selected from the group of radiation-shielding powders specified in the present invention and a non-powdered silica-based binder. Then, a composite having a high content of radiation-shielding powder with an aluminum matrix or the like can be provided, which is configured by impregnating and filling all of the voids of the porous molded body (preform) with at least one molten low-melting-point metal having a melting point of 200° C. or more and 900° C. or less, selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin, and lead, and then solidifying to form a composite. In addition, a composite having a different configuration having a high content of radiation-shielding powder can be provided in which at least 25 volume % of the voids in the porous molded body (preform) described above is impregnated with a liquid organic / inorganic sealing agent, and then the preform is heated to a temperature of 200° C. or more and 900° C. or less, whereby the liquid organic / inorganic sealing agent is solidified and composited.
[0028] Furthermore, in the case of any of the composites having the above-mentioned configurations, the non-powdered silica-based binder used in preparing the preform has a property of being able to form the preform at a temperature at which the radiation-shielding powder used in the composite is not decomposed, and thus the following effects can be obtained. That is, by being configured in this way, the composite having the radiation-shielding function of the present invention has high strength in which the radiation-shielding powder specified in the present invention is bound by aluminum or an organic / inorganic sealing agent, and in addition, the radiation-shielding powder used is not decomposed and can be used at high temperatures of 300°C or more. Hereinafter, the term "molten aluminum" or "molten aluminum" in the specification of the present invention is described with molten aluminum metal as a representative example. That is, in the specification of the present invention, the term "molten aluminum" or "molten aluminum" is described to include not only molten aluminum metal but also molten aluminum of a low-melting point metal selected from the group consisting of aluminum alloys, zinc, tin, and lead, or a low-melting point alloy of the low-melting point metal and other metals (for example, low-melting point alloy solders mainly composed of tin or lead, and zinc alloys). In the specification of the present invention, the term "molten aluminum" refers to a low-melting-point metal or low-melting-point alloy having a melting point of 200° C. or higher. In the present invention, it is preferable to use a low-melting-point metal or low-melting-point alloy having a melting point of 300° C. or higher. That is, according to the studies of the present inventors, when a low-melting-point metal or low-melting-point alloy having a melting point of less than 300° C. is used, the heat resistance of the obtained composite may not be sufficient depending on the application, which is not preferable.
[0029] The fourth feature of the present invention is that, according to the study by the present inventors, when aluminum metal or aluminum alloy melted at high temperature is used as the molten metal for compounding with radiation-shielding powder, the following problem occurs, but this problem has been solved. According to the present invention, even radiation-shielding powders such as boron carbide which generates Al4C3 that shows a decomposition reaction with moisture in the air when reacting with aluminum, barium sulfate which reacts with molten aluminum at high temperatures to decompose into Al2O3, BaO and SO2, and strontium sulfate, tungsten, iron powder, and aluminum borate which undergo oxidative degradation, thermal decomposition, and generation of unstable substances at temperatures above 900°C can be used as raw materials, and a composite can be produced that can be stably used at temperatures of 300°C or higher. Therefore, since it is possible to use a wide variety of radiation-shielding powders as specified in the present invention, the present invention can significantly expand the application range of the composite. [Brief description of the drawings]
[0030] FIG. 1 is a schematic diagram showing how molten aluminum 1 is cast into a preform 2 in the first production method. [Figure 1A] 1 is a schematic diagram showing how a heated preform 2 is placed in a mold of a press 10 and molten aluminum 1 is poured into it. [Figure 1B] 1 is a schematic diagram showing how molten aluminum 1 is cast into a preform 2 using an upper punch 5 and a lower punch 4 of a high-pressure press, and then impregnated therewith. [Figure 1C] FIG. 13 is a schematic diagram showing how, after cooling, lower punch 4 is pushed up to remove composite 3 in a state in which the impregnated molten aluminum has solidified. [Diagram 2] FIG. 1 is a schematic diagram for illustrating an outline of a reduced pressure vessel 30 used when impregnating voids in a preform 2 with a liquid organic / inorganic sealing agent 32, which is performed in the second manufacturing method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Preferred embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0032] The radiation-shielding composite of the present invention is a composite having a radiation-shielding function, which contains a total of 3 volume % or more and 85 volume % or less of powders having a radiation-shielding effect, and is composed of gadolinium oxide (Gd2O3) powder, boron carbide (B4C) powder, boron oxide (B2O3) powder, boron (B) powder, barium sulfate (BaSO4) powder, strontium oxide (SrO) powder, tungsten (W) powder, tungsten oxide (W2O3) powder, tungsten carbide (WC) powder, molybdenum (Mo) powder, molybdenum oxide (MoO3) powder, iron (Fe) powder, iron oxide (Fe2O3) powder, and ferrite powder mainly composed of iron oxide, which have the radiation-shielding effect. a porous molded body (preform) which is a molded and sintered product made of a mixture containing one or more types of radiation-shielding powders selected from the group and a non-powdered silica-based binder, and all of the voids of the porous molded body (preform) are impregnated and filled with molten aluminum, and then solidified to form a composite, or a porous molded body (preform) which is impregnated with a liquid organic / inorganic sealing agent at least 25 volume % of the voids of the porous molded body (preform), and then solidified to form a composite, and the non-powdered silica-based binder is characterized in that it can form the porous molded body (preform) (hereinafter simply referred to as a preform) which is the molded and sintered product at a temperature at which the radiation-shielding powder is not decomposed.
[0033] The composite having a radiation-shielding function of the present invention having the above-mentioned configuration can be obtained in a stable manner while suppressing decomposition of the radiation-shielding powder by the production method of the present invention comprising, for example, the first or second means described below. Therefore, a good quality composite that meets the intended use and provides the various effects of the present invention described above can be easily and stably prepared.
[0034] The radiation-shielding composite of the present invention, which is configured by impregnating and filling all of the voids in the preform having the specific configuration described above with "molten aluminum" and solidifying it to form a composite, can be easily and stably prepared by the first manufacturing method of the present invention described below. As described above, "molten aluminum" and "molten aluminum" refer to at least any molten aluminum metal, aluminum alloy, low-melting-point metal, and low-melting-point alloy, each having a melting point of 200°C or higher, preferably 300°C or higher and 900°C or lower.
[0035] The first manufacturing method of the present invention is a method for preparing a composite having a radiation-shielding function, which contains an aluminum matrix and a powder having a radiation-shielding effect in a total amount of 3 volume % or more and 85 volume % or less, and the method comprises adding a non-powdered silica-based powder to one or more of the powders having a radiation-shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron oxide powder, boron powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide. The method is characterized by comprising the steps of: molding the mixture obtained by adding and mixing a binder, and then firing the obtained molded body at a temperature of 300°C or more and 900°C or less to produce a porous molded body (preform); and casting molten aluminum into the preform obtained in the step at a temperature of 300°C or more and 900°C or less, and holding the preform at a high pressure of 20 MPa or more and 200 MPa or less for 3 to 15 minutes, for example, 3 to 5 minutes, in order to impregnate the preform with the molten aluminum, and then immediately removing the composite in a state in which the molten aluminum has been impregnated and cooling it to suppress decomposition of the radiation shielding powder in the composite and generation of unstable substances such as Al4C3.
[0036] In the first manufacturing method of the present invention, further, in the step of preparing the preform, aluminum powder, aluminum alloy powder, or ceramic powder may be added to the radiation-shielding powder, and the preform may be prepared by adding 0.5 to 10 mass% of the non-powdered silica-based binder in terms of SiO2 when the total of the aluminum powder, aluminum alloy powder, or ceramic powder, and the radiation-shielding powder is 100 mass%. By configuring in this way, it is possible to more easily prepare a composite having a radiation-shielding function, which contains aluminum or an aluminum alloy as a matrix and a powder having a radiation-shielding effect, the powder being appropriately controlled in a total amount within a range of 3 volume% to 85 volume%. This will be described later.
[0037] The composite having a radiation shielding function of the present invention, which is configured by impregnating at least 25% by volume of the voids of the preform having the specific configuration described above with a liquid organic / inorganic sealing agent and solidifying it to form a composite, can be simply and stably prepared by the second manufacturing method of the present invention described below.
[0038] The second manufacturing method of the present invention is a method for manufacturing a composite having a radiation-shielding function, which comprises preparing a composite containing a total of 3 volume % or more and 85 volume % or less of a composite of powders having a radiation-shielding effect, the powders being formed by compounding the powders, and the composite is formed by adding a non-powdered silica-based binder to one or more types of powders having a radiation-shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron oxide powder, boron powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide, and then molding the mixture obtained. the step of baking the molded body obtained in the step of producing a porous molded body (preform) at a temperature of 300°C or more and 900°C or less, and a step of vacuum-impregnating a liquid organic / inorganic pore-sealing agent containing 30% by mass or more of non-volatile components and having a viscosity of 50 mPa s or less into voids of the preform obtained in the step of producing the preform, or impregnating the preform at a pressure of 10 atmospheres or less by pressurizing after vacuum impregnation, and then heating the preform at a temperature of 300°C or more and 900°C or less, so that a solidified product of the liquid organic / inorganic pore-sealing agent and / or a heat-treated product of the liquid organic / inorganic pore-sealing agent remains in an amount of 25% by volume or more relative to 100% by volume of the voids of the preform, thereby compositing the radiation-shielding powder with a component derived from the liquid organic / inorganic pore-sealing agent.
[0039] <Process for producing porous molded body (preform)> The details of the first and second manufacturing methods of the composite having a radiation shielding function of the present invention will be described below. As described above, the steps of manufacturing a porous molded body (preform) constituting the first and second manufacturing methods are the same. Therefore, the step of manufacturing a preform will be described first.
[0040] [Raw radiation shielding powder, etc.] In the present invention, as the radiation shielding powder used as the raw material for producing the preform, one or more selected from the group consisting of gadolinium oxide (Gd2O3) powder, boron carbide (B4C) powder, boron oxide (B2O3) powder, boron powder, barium sulfate (BaSO4) powder, strontium oxide (SrO) powder, tungsten (W) powder, tungsten oxide (W2O3) powder, tungsten carbide (WC) powder, molybdenum (Mo) powder, molybdenum oxide (MoO3) powder, iron (Fe) powder, iron oxide (Fe2O3) powder, and ferrite powder mainly composed of iron oxide are used. In the prior art, lead powder or lead oxide powder is generally used alone as the radiation shielding powder. However, in the present invention, the use of these radiation-shielding powders is not used because the weight of the structure (composite) would increase and there is a concern about the impact on the environment. In addition, these materials have low melting points and are therefore unsuitable for the manufacturing method of the present invention, which is useful for effectively obtaining the composite of the present invention.
[0041] In the present invention, in addition to the radiation-shielding powders listed above, aluminum powder, aluminum alloy powder, or ceramic powder can be added to reduce the filling rate of the radiation-shielding powder in the composite. In this way, it becomes possible to freely control the filling rate (volume rate) of the radiation-shielding powder constituting the composite of the present invention to a wide range. In this case, in the manufacturing process of the porous molded body (preform) constituting the manufacturing method of the present invention, aluminum powder, aluminum alloy powder, or ceramic powder is further added as necessary to the specific radiation-shielding powder specified in the present invention, and 0.5 to 10 mass % (w%) of the non-powdered silica-based binder in terms of SiO2 is added to the total volume 100v% of these powders to manufacture the preform. The manufacturing method is the same as the manufacturing method of the composite of the present invention, except that aluminum powder, aluminum alloy powder, or ceramic powder is used as necessary. For this reason, in the following explanation, a method of manufacturing a preform including the above-mentioned optional configuration will be explained.
[0042] The average particle size of the radiation-shielding powder used in the manufacturing method of the present invention and the aluminum powder, aluminum alloy powder, or ceramic powder used as necessary (hereinafter also referred to as "aluminum powder, etc.") is preferably 0.3 μm or more and 500 μm or less. The reason for setting the average particle size to 0.3 μm or more is that materials with an average particle size smaller than that tend to aggregate with each other and tend to become so-called lumps in an aggregated state, and when two or more types of powder are used, it is undesirable because it may be difficult to uniformly mix them. In addition, there is a tendency that it becomes difficult to uniformly mix the silica-based binder added to the above-mentioned powder (powder). In addition, when a powder with an average particle size of less than 0.3 μm is used, the powder filling rate in the preform obtained by molding by press molding, CIP molding, casting molding, etc. tends to be low, so there is a risk that it will not be possible to produce a preform with a high volume fraction (Vf) of the radiation-shielding powder, which is a feature of the present invention. On the other hand, when a large powder exceeding 500 μm is used, the powder packing property is poor, and there is a risk that a preform with high Vf cannot be produced, as in the case of using a powder with a too small average particle size. In addition, according to the study by the present inventors, since the above-mentioned coarse particles have a small surface area, the binder effect of the silica-based binder added to the radiation shielding powder and the aluminum powder used as necessary is low, and it becomes impossible to produce a strong preform, which is also undesirable in this respect.
[0043] The "average particle size" of the radiation-shielding powder and the aluminum powder used as necessary in the present invention is the particle size (median size) at an integrated value of 50% in the particle size distribution determined by a laser diffraction / scattering method.
[0044] Although it varies depending on the type and particle size of the radiation-shielding powder, according to the study by the present inventors, the volume fraction (Vf) of the preform usually obtained in the preform manufacturing process constituting the manufacturing method of the present invention is generally about 50v%. According to the study by the present inventors, when the volume fraction Vf of the radiation-shielding powder in the preform is increased, it is preferable to mix particles with a large average particle size and particles with a small average particle size so that the small particles are mixed between the large particles. In addition, in the present invention, when two or more types of radiation-shielding powder are mixed, the same type of radiation-shielding powders having different average particle sizes may be mixed, or different types of radiation-shielding powders may be mixed. When it is desired to produce a preform with a required Vf in the present invention, a test mix may be performed in advance and the mixture of particles used to produce the preform may be determined by calculating from the bulk density of the preform. According to the investigations of the present inventors, by using the manufacturing method of the present invention, it is possible to produce a preform with a Vf of up to 85v% by appropriately mixing particles, and as a result, it becomes possible to provide a composite with a high content of radiation-shielding powder, which could not be produced by conventional techniques up to now.
[0045] In the use of a composite having a radiation shielding function, various situations are considered. For example, the higher the volume fraction (Vf) of the radiation shielding powder in the structure having a radiation shielding function, the greater the radiation shielding effect. However, depending on the application, there may be cases where a low Vf is acceptable, or cases where the Vf of the radiation shielding powder is lowered in consideration of production costs. In contrast, according to the embodiment of the manufacturing method of the present invention, in which aluminum powder or the like is used as necessary, the content of the radiation shielding powder in the manufactured preform can be appropriately controlled within a wider range by a very simple means of adding a required amount of aluminum powder or the like to the specific radiation shielding powder specified in the present invention. For example, a preform with a radiation shielding powder Vf of 50v% will be impregnated with 50v% molten aluminum in the next process. In contrast, for example, when a preform formed by adding aluminum powder is used, the total amount of aluminum in the preform and the molten aluminum metal or aluminum alloy or specific low melting point metal or specific low melting point alloy impregnated in a later process (referred to in the specification of the present invention as "molten aluminum") becomes the amount of aluminum in the composite, so that the amount of aluminum in the structure having a radiation shielding function made from the composite can be increased. In other words, by adding aluminum powder or the like to the preform, it becomes possible to freely control the volume fraction Vf in the structure having a radiation shielding function.
[0046] As described above, for example, by adopting a combination of large and small particles of a specific radiation-shielding powder, or by appropriately using means such as adding aluminum powder or the like as necessary, according to the manufacturing method of the present invention, it is possible to easily manufacture a composite of radiation-shielding powder and molten aluminum, in which the blending amount of the radiation-shielding powder is controlled in a wide range of Vf (filling rate) from 3v% to 85v%. According to the study by the present inventors, a composite with a content of radiation-shielding powder of less than 3v% is not practical because the radiation shielding effect is too low. In addition, according to the study by the present inventors, it is difficult to achieve a Vf of 85v% or more with conventional techniques, even if particle blending and various molding methods are used.
[0047] [Preform manufacturing process] In the step of producing a preform constituting the manufacturing method of the present invention, first, a material for forming the preform is prepared as follows. One or more types of powder are selected from the specific radiation-shielding powder group described above and specified in the present invention, and aluminum powder or the like added as necessary is thoroughly stirred and mixed with a ball mill, a paddle-type mixer, or the like. For example, when tungsten powder (specific gravity: 19.3) and boron carbide powder (specific gravity: 2.52) with different specific gravities are used as the radiation-shielding powder, and aluminum powder (specific gravity: 2.7) is mixed as necessary, it is preferable to use a V-type mixer or a drum can rotary mixer in which the entire mixing container rotates in order to prevent separation due to the difference in specific gravity.
[0048] Next, a mixture of the radiation-shielding powder defined in the present invention and aluminum powder or the like, which is used as necessary, is mixed with a non-powdered silica-based binder to form a molded mixture, and the molded body obtained is fired at a temperature of 300° C. or higher and 900° C. or lower to produce a porous molded body (preform). The configurations of these components are described below.
[0049] (Non-powdered silica-based binder) The non-powdered silica-based binder constituting the present invention is suitably at least one liquid silica-based binder selected from the group consisting of water glass (sodium silicate), colloidal silica, liquid silicone resin, a silicone resin solution obtained by dissolving a silicone resin in an organic solvent, and silica alkoxides made of silica and organic matter and cured by heating at a temperature of 900° C. or less (hereinafter also referred to as “liquid silica-based binders”). The liquid silica-based binder is added in a required amount according to the amount of the radiation-shielding powder, etc., used.
[0050] The amount of the liquid silica-based binder used in the present invention is, for example, about 0.5 to 10 parts by mass, calculated as SiO2, per 100 parts by mass of the mixture powder of the radiation-shielding powder containing aluminum powder or the like as necessary. According to the study by the present inventors, an amount of less than 0.5 parts by mass is not preferable because the strength exhibited as a binder is small. On the other hand, even if the amount exceeds 10 parts by mass, the binder function is exhibited, but the relative content of the radiation-shielding powder is low, so there is no need to add more than this.
[0051] Liquid silica-based binders such as the above-mentioned ethyl silicate are compounds of silica (Si) and organic matter, which are thermally decomposed to become ultrafine powder SiO2. Water glass becomes ultrafine powder SiO2 binder when heated with sodium silicate dissolved in water. As colloidal silica, it is preferable to use one in which extremely fine silica particles of several tens of μ (nm) or less are dispersed as colloids in water or an organic solvent. The reason for using these silica-based binders is to strengthen the preform to be used in the next process.
[0052] By using ethyl silicate or silicone resin, which contains silica that is thermally decomposed at low temperatures and changes to SiO2, or colloidal silica of ultrafine SiO2 dispersed in water glass or a solvent, which also produces SiO2 at low temperatures, the binder and the radiation shielding powder can be mixed uniformly. According to the study by the present inventors, these silica-based binders are ultrafine powders, and in the process of the manufacturing method of the present invention, they go from a state where they are uniformly mixed in the preform at the molecular level to an amorphous (non-crystalline) state, and then ultrafine powder SiO2 is produced while remaining uniform, so that a strong preform can be produced.
[0053] In the next step, the mixed powder, which is the raw material of the preform prepared above, is molded and fired to prepare a preform. What is important in the present invention is to prevent decomposition of the radiation shielding powder in the process of manufacturing the composite of the present invention so that the function targeted by the present invention is not impaired. For this reason, in the manufacturing method of the present invention, the firing temperature when molding and firing to prepare a preform needs to be a low temperature of 900°C or less. In contrast, all of the liquid silica-based binders used in the present invention can fully exert their binder effect even at 900°C or less. Here, when using a silica-based binder in the manufacturing process of ordinary ceramics, silica powder of submicrons to several μm is generally used. And, in the conventional technology, when using silica powder as a binder, it is necessary to prepare a preform by firing at a temperature of 1100°C or more in order to exert the strength of the obtained preform. However, the above-mentioned conventional technology cannot be applied to the technology of the composite of the present invention. In the manufacturing method of the present invention, when preparing a preform by molding and sintering, and when impregnating the prepared preform with molten aluminum, it is necessary to prevent decomposition of the radiation-shielding powder, so the temperature must be low, 900° C. or lower. This will be described later.
[0054] In the manufacturing method of the present invention, the liquid silica-based binder as described above is added little by little to one or more types of uniformly mixed radiation shielding powder that may contain the above aluminum powder, etc. The mixer used in this case is preferably a Henschel mixer that stirs at high speed with high shear force, or a mixer equipped with a birdcage-shaped rotor made of thin wires. When adding the liquid silica-based binder, an appropriate amount of an organic binder such as PVA or PVB may be added as necessary within a range that does not impair the object of the present invention.
[0055] Next, the mixture containing the radiation-resistant shielding powder obtained by adding the liquid silica-based binder and uniformly mixing it as described above is used to produce a molded body by a general method such as press molding, tapping molding, CIP molding, etc.
[0056] In the manufacturing method of the present invention, the molded body obtained as described above is heated and sintered at a temperature of 300°C to 900°C, and hardened to produce a preform. According to the study by the present inventors, at a temperature below 300°C, the effect of the silica-based binder cannot be exerted, and a strong preform cannot be produced. On the other hand, at a temperature of 300°C or higher, the effect of the added liquid silica-based binder is exerted, and a strong preform can be produced. In addition, for the following reasons, in the manufacturing method of the present invention, it is necessary to produce a preform by sintering at a temperature of 900°C or lower.
[0057] For example, when boron carbide (B4C) is used as the radiation shielding powder, it may decompose into BO and CO2 at high temperatures in air, so it must be fired at a temperature of 900°C or less. In addition, when boron carbide (B4C) is used as the material for forming the preform and aluminum powder or the like is added as necessary, Al4C3 formed from boron carbide and aluminum may undergo the following decomposition reaction at high temperatures. The Al4C3 generated by the following decomposition reaction is unstable and reacts with moisture in the air to decompose into Al(OH)3 and CH3. However, it is not desirable for Al4C3 to remain in the composite. B4C+Al → Al4C3+B
[0058] In addition, when barium sulfate is used as the radiation shielding powder, BaSO4 decomposes into BaO and SO2 at high temperatures, so in this case too, it is not recommended to sinter at high temperatures. In addition, it is not recommended to sinter at high temperatures above 900°C, as the following decomposition reaction may occur. Al+BaSO4→BaO+Al2O3+SO(gas)
[0059] When tungsten (W) is used as the radiation shielding powder, tungsten becomes WO3 at high temperatures in air, which is undesirable since it reduces the effect of adding a silica-based binder. According to the study by the present inventors, in order to suppress the above-mentioned series of reactions, it is preferable to set the firing temperature of the molded body to 900°C or less. By doing so, decomposition and oxidation are suppressed, and it is possible to manufacture a stable preform of radiation shielding powder.
[0060] <Complex preparation process> Next, in the first production method of the present invention, molten aluminum is impregnated and filled into all of the voids of the porous molded body (preform) produced as described above at high pressure, and then solidified to produce a composite having a radiation shielding function. In the second production method of the present invention, a liquid organic / inorganic sealing agent is vacuum-impregnated into some or all of the voids of the preform, or the liquid organic / inorganic sealing agent is impregnated under pressure after vacuum impregnation, and then the sealing agent is heated to a temperature of 300° C. or higher and 900° C. or lower to solidify and compound the voids. Hereinafter, the steps for producing the composite in the first production method of the present invention and the second production method of the present invention will be described respectively.
[0061] [First manufacturing method] In the first manufacturing method of the present invention, a composite having a radiation shielding function is prepared, which contains aluminum as a matrix and a powder having a radiation shielding effect in a range of 3 volume % or more and 85 volume % or less in total. Specifically, a preform prepared as described above is used, and a molten metal of a low melting point metal selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin and lead, or a low melting point alloy of the low melting point metal and other metals (in the present specification, a molten metal containing these molten metals is also called "molten aluminum" representing aluminum metal and aluminum alloy) is cast into the preform at a temperature of 300°C to 900°C, and the molten aluminum is impregnated into the entire voids of the preform at a high pressure of 20 MPa to 200 MPa for 3 to 15 minutes, for example, about 3 to 5 minutes, and then immediately removed within 15 minutes after the start of impregnation with the molten aluminum and cooled to obtain a composite. More specifically, the composite is formed by the following procedure.
[0062] The temperature of the molten aluminum to be impregnated is set to a temperature higher than the melting point of each metal, usually about 50°C to 150°C higher than the melting point of each metal. For example, in the case of aluminum metal or aluminum alloy, the temperature is about 700°C to 800°C. In addition, in the case of using a low melting point alloy, it is appropriate to set the temperature to about 350°C to 500°C for solder alloy and about 450°C to 550°C for zinc alloy. Regardless of the type of molten metal used, in the present invention, it is necessary to impregnate the voids of the preform produced as described above with the molten metal at 900°C or less.
[0063] First, the preform previously prepared is preheated at a temperature of 300°C or more and 900°C or less in order to be impregnated with the molten aluminum. If the preform is preheated at a low temperature of less than 300°C, the molten aluminum impregnated in the process of casting and impregnating the molten aluminum described below is cooled and solidified quickly, which is not preferable because it is difficult to impregnate the entire voids of the preform. According to the study by the present inventors, if the preform is preheated at a temperature of 300°C or more, the molten aluminum impregnates the entire voids of the preform. However, if the preheating temperature exceeds 900°C, for example, boron carbide, which is a radiation shielding powder, reacts with the aluminum impregnated with the molten aluminum to generate Al4C3, or BaSO4 may decompose. This is not preferable.
[0064] Next, the process of impregnating the preheated preform with molten aluminum to form a composite will be described with reference to Fig. 1. Specifically, the preform produced as described above is impregnated with molten aluminum in the following order to form a composite.
[0065] (1) As shown in Fig. 1A, a preform 2 preheated at 300°C to 900°C is placed on a lower punch 4 of a press die 10 that has been preheated to about 200°C to 300°C with a burner or the like. Next, molten aluminum 1 melted at a temperature of 300°C to 900°C is cast into the press die 10. When using aluminum metal or an aluminum alloy, molten aluminum at a temperature of 700°C to 900°C is preferably used. (2) Next, as shown in Fig. 1B, an upper punch 5 of a press 10 is placed and a load is applied. A load is applied to the upper punch 5 of the press 10 so that the pressure of the molten aluminum 1 becomes 20 MPa to 200 MPa, and the molten aluminum 1 is impregnated into the pores (gaps) of the preform 2. At this time, the state in which the load is applied is maintained for 3 minutes to 15 minutes in order to impregnate the molten aluminum 1 into the voids of the preform 2. (3) Next, as shown in Fig. 1C, immediately after the preform 2 is impregnated (specifically, within about 15 minutes after the start of impregnation with the molten aluminum), the lower punch 4 is pushed up from its bottom, and the composite 3 impregnated with the molten aluminum 1 is immediately removed. Then, the composite 3 is cooled in as short a time as possible to solidify the impregnated molten aluminum 1.
[0066] Below, points to be noted in the process of impregnating the molten aluminum 1 into the preform 2, which is a series of porous molded bodies, as described above, are explained. First, when aluminum metal or aluminum alloy is used, a casting temperature of less than 600°C is not preferable because the molten aluminum hardens in a short time and does not impregnate the entire voids of the preform. On the other hand, a casting temperature of more than 900°C is not preferable because, as explained above, for example, boron carbide (B4C) in the radiation shielding powder may decompose to produce Al4C3, or if barium sulfate (BaSO4) is used as the radiation shielding powder, BaSO4 may thermally decompose.
[0067] In the first manufacturing method of the present invention, the pressure for impregnation of the molten aluminum is 20 MPa or more and 200 MPa or less. If the pressure is less than 20 MPa, the molten aluminum may not be impregnated into the entire voids of the preform due to the pressure being too low, which is not preferable. Since impregnation is sufficient at 20 MPa or more and 200 MPa or less, there is no need to apply pressure exceeding 200 MPa. According to the study by the present inventors, good impregnation can be achieved even at a pressure of about 100 MPa, for example.
[0068] The composite obtained by high pressure impregnation is held for 3 minutes, preferably for about 5 minutes, and then removed from the mold within at least 15 minutes from the start of impregnation with the molten aluminum. If the composite obtained by high pressure impregnation of the voids in the preform with the molten aluminum is held in the mold for a long time exceeding 15 minutes, for example, boron carbide and aluminum may react to generate Al4C3, or BaSO4 may decompose, resulting in a composite that violates the provisions of the present invention, and this must be avoided.
[0069] In the above description, a method of high-pressure impregnation of a porous molded body (preform) with molten aluminum using a high-pressure press as shown in FIG. 1 has been exemplified. However, the present invention is not limited to this, and any configuration that allows molten aluminum to be cast and filled into a preform at 20 MPa or more may be used, for example, a die-casting machine, a squeeze-casting machine, or the like may be used. The cooled composite is surrounded by aluminum, which is removed by machining to extract the composite. According to the first manufacturing method of the present invention described above, a stable and dense composite having radiation shielding function and containing a radiation-shielding powder with a Vf of 3% to 85v% can be produced.
[0070] [Second manufacturing method] In the second manufacturing method of the present invention, a composite having radiation shielding function is prepared, which is formed by compounding a powder having radiation shielding effect in a total range of 3 volume % or more and 85 volume % or less, in which a solidified material resulting from a liquid organic / inorganic sealing agent is present in an amount of 25 volume % or more relative to 100 volume % of voids in the preform obtained as described above.
[0071] (liquid organic / inorganic sealant) In the second production method of the present invention, it is preferable to use, as the liquid organic / inorganic sealing agent which characterizes the second production method, three types of liquid compounds having a low viscosity of 50 mPa s or less and containing 30 mass % or more of non-volatile components, such as those listed below. (1)Type 1 Liquid ethyl silicate [Si(OC2H5)4] having an alcohol Si bond or liquid oligomers obtained by partial hydrolysis of said ethyl silicate into dimers or tetramers, similar liquid alkoxides such as methyl silicate [Si(OCH3)4] and liquid oligomers obtained by partial hydrolysis thereof, etc., which are adjusted so that the non-volatile components are 30 mass% or more.
[0072] (2) Type 2 Liquid silicone or its derivatives having a siloxane bond as the main chain of the following general formula, or silicone or its derivatives adjusted so that the non-volatile components when diluted and dissolved in a solvent are 30 mass% or more. R in the general formula is an organic group such as a methyl group, an ethyl group, a vinyl group, a phenyl group, an acetyl group, etc. Specifically, for example, liquid compounds such as silicone oil or a silicone adhesive dissolved in an organic solvent can be used. TIFF0007606793000001.tif23170
[0073] (3) Type 3 A liquid alkoxysilane compound that is an alkoxysilane derivative and reacts with moisture in the air to undergo a condensation reaction to generate a silicone oxygen organic compound (Si-OR) as shown in the reaction formula below. For example, a compound such as a one-part room temperature curing sealant described in Japanese Patent No. 3816354 can be used. As such a compound, for example, a commercially available product such as Permeate (registered trademark, manufactured by D&D Co., Ltd.) can be used.
[0074] TIFF0007606793000002.tif105170
[0075] (Method of compounding) In the second manufacturing method of the present invention, a composite having a radiation shielding function is obtained in which a solidified material originating from a liquid organic inorganic pore-sealing agent is present in the voids of a preform produced as described above using a radiation-shielding powder as a raw material. As a specific procedure, a liquid organic inorganic pore-sealing agent containing 30 mass% or more of a non-volatile component and having a viscosity of 50 mPa·s or less is vacuum-impregnated into the voids of a porous molded body (preform), or impregnated at a pressure of 10 atmospheres or less by applying pressure after vacuum impregnation, and then heated to a temperature of 300°C or more and 900°C or less, so that the solidified material of the liquid organic inorganic pore-sealing agent and / or the heat-treated material of the liquid organic inorganic pore-sealing agent remain in 25 volume% (1 / 4) or more of the entire voids when the entire voids of the preform are taken as 100 volume%, thereby composing the radiation-shielding powder and the component originating from the liquid organic inorganic pore-sealing agent. That is, the ratio of the total voids in the preform is about 15v% to 40v%, so that the components derived from the organic and inorganic sealant remain in the voids at 1 / 4 or more of the total, that is, 4v% to 10v% or more. In other words, the obtained composite has a high ratio of 60v% to 85v% of the fired mixture containing the radiation-shielding powder constituting the preform, 4v% to 10v% or more of the components derived from the organic and inorganic sealant, and the remainder is voids. In addition, the amount of the liquid silica-based binder mixed with the radiation-shielding powder is preferably about 0.5 to 10 parts by mass in terms of SiO2 added to 100 parts by mass of the radiation-shielding powder in the present invention, so that a composite having a high ratio of the radiation-shielding powder can be obtained. These points are the same for the composite obtained by the first manufacturing method.
[0076] The liquid organic / inorganic sealing agent used in the second manufacturing method of the present invention, as exemplified above, has a low viscosity of 50 mPa·s or less so that it can be easily impregnated into the preform. If the viscosity exceeds 50 mPa·s, the organic / inorganic sealing agent is unlikely to be impregnated into the fine parts of the preform, and a strong composite may not be obtained. In addition, it is essential that the liquid organic / inorganic sealing agent contains 30 wt% or more of non-volatile matter relative to 100 wt% of the sealing agent. In the second manufacturing method of the present invention, the organic / inorganic sealing agent is impregnated into the voids so that it is present at least 25 v% relative to the entire voids of the preform (100 v%), and then heated to 200°C to 900°C to composite the radiation shielding powder and the organic / inorganic sealing agent. That is, by heating at the above-mentioned temperatures, the liquid organic / inorganic sealing agent impregnated in the voids of the preform becomes a solidified liquid organic / inorganic sealing agent or a heat-treated liquid organic / inorganic sealing agent, both of which are solid, and remains in the voids of the preform.
[0077] The preform used in the manufacturing method of the present invention, which is prepared as a composite as described above, is a porous body in which voids are present in about 15 to 40 v % relative to 100 v % of the entire preform. Therefore, the composite obtained by the second manufacturing method of the present invention, in which a liquid organic inorganic sealing agent is impregnated into the preform and then heat-treated, is a composite in which the solidified liquid organic inorganic sealing agent and / or the heat-treated liquid organic inorganic sealing agent are present in a proportion of 25 v % or more when the entire voids of the preform are taken as 100 v %. This means that the composite obtained by the second manufacturing method of the present invention is a composite in which the solidified liquid organic inorganic sealing agent and / or the heat-treated liquid organic inorganic sealing agent are fixed to a part (25 v % or more) or all of the voids of the preform.
[0078] According to the study by the present inventors, when the amount of the solidified liquid organic inorganic sealing agent and / or the heat-treated liquid organic inorganic sealing agent in the composite obtained by the second manufacturing method of the present invention is less than 25v% relative to the entire voids of the preform (100v%), a composite having a strong and practical radiation shielding function cannot be obtained. In addition, a preferred configuration of the composite obtained by the second manufacturing method of the present invention is that the amount of the solidified liquid organic inorganic sealing agent and / or the heat-treated liquid organic inorganic sealing agent remaining in the voids is about 5v% or more relative to the entire preform (100v%). For example, when the proportion of voids in the preform is 20v%, 25% (1 / 4) of that, that is, 5v% relative to 100v% of the preform, is the organic inorganic sealing agent. In the above example, the fired product of the mixture containing the radiation-shielding powder constituting the preform accounts for 80v%. As mentioned above, the amount of liquid silica-based binder to be mixed with the radiation-shielding powder when preparing the preform is preferably about 0.5 to 10 parts by mass of the liquid silica-based binder in terms of SiO2 to 100 parts by mass of the radiation-shielding powder. Therefore, the total amount of the radiation-shielding powder, silica-based binder, and organic / inorganic sealing agent constituting the composite of the above example shows a high ratio of 70 to 79.5v%, resulting in a strong composite.
[0079] In the second manufacturing method of the present invention, the silica-based binder required for producing the preform and the liquid organic / inorganic sealant to be impregnated into the obtained preform may be the same compound. However, the liquid organic / inorganic sealant used for impregnating the voids in the preform must be impregnated into the preform so that the sealant impregnated into the voids in the preform must remain in a solidified state, and therefore must have a low viscosity of 50 mPa·s or less and a non-volatile content of 30 wt% or more. Therefore, any silica-based binder that meets these requirements can be used in common.
[0080] As described above, in the second manufacturing method of the present invention, the preform impregnated with the liquid organic / inorganic sealing agent is heated at a temperature of 200°C or more and 900°C or less. The reason why the heating temperature is set to 200°C or more in this case is as follows. By setting the heating temperature to 200°C or more, the liquid alkoxysilane compound that generates siloxane bonds, ethyl silicate oligomers, or silicone oxygen organic compounds (Si-OR) in the compound used as the liquid organic / inorganic sealing agent is thermally decomposed, and the compound functions as a silica-based binder or a Si-OR-based organic / inorganic binder, thereby strengthening the preform. In addition, the reason why the heating temperature is set to 900°C or less is to prevent the powder having a radiation shielding effect, including B4C and BaSO4, constituting the preform, from being decomposed or oxidized.
[0081] The procedure of the second manufacturing method of the present invention will be described with reference to FIG. 2. In FIG. 2, 30 is a reduced pressure vessel used in the second manufacturing method of the present invention. A preform 32 is placed in an interior vessel 34 placed in the reduced pressure vessel 30 before the organic and inorganic sealing agent 31 is impregnated into the gaps. The opening and closing jig 33 of the reduced pressure vessel 30 is closed, and the reduced pressure vessel 30 is depressurized from a pressure reduction port 36 provided in the reduced pressure vessel 30 using a vacuum pump (not shown). When the reduced pressure vessel 30 is reduced to approximately zero atmospheric pressure, the organic and inorganic sealing agent 31 is gradually introduced from an organic and inorganic sealing agent introduction vessel 35 into the interior vessel 34. At this time, the amount of the organic and inorganic sealing agent 31 introduced is predicted in advance so that the organic and inorganic sealing agent 31 is completely impregnated into the preform 32 and the entire preform 32 is immersed therein.
[0082] After the organic and inorganic sealing agent 31 is charged as described above, the vacuum is maintained for about 5 to 10 minutes, and the organic and inorganic sealing agent 31 is vacuum-impregnated into the voids of the preform 32. After the impregnation is completed, the pressure is gradually opened to the atmosphere, and air is introduced into the reduced pressure vessel 30. After the inside of the reduced pressure vessel 30 becomes atmospheric, air decompressed to about 10 atmospheres with compressed air from a compressor or the like (not shown) is gradually introduced from the pressure port 37, and after pressurizing to about 4 atmospheres, the pressure is kept for about 5 to 10 minutes, and the organic and inorganic sealing agent 31 is impregnated into the preform 32.
[0083] Thereafter, the compressed air in the reduced pressure vessel 30 is gradually released, and once atmospheric pressure is reached, the preform having the solidified liquid organic / inorganic sealing agent and / or the heat-treated liquid organic / inorganic sealing agent fixed in the voids is taken out, gradually dried, and heated to 300 to 400°C to obtain a composite having a radiation shielding function. EXAMPLES
[0084] Next, the present invention will be described in more detail with reference to examples and comparative examples. The present invention will be specifically described with reference to examples and comparative examples of two manufacturing methods: a method of impregnating molten aluminum into the voids of a porous molded body (preform), which is a molded and fired product made of a mixture containing a non-powdered silica-based binder in a radiation-shielding powder, and a method of impregnating an organic / inorganic sealing agent. The present invention is not limited in any way by the following examples. In the text, % means volume % unless otherwise specified. Due to the special circumstances that require handling radiation in measuring the shielding effect, the radiation shielding rate of the composites of Examples 1 to 3 was requested to be measured by an external measuring institution. The radiation shielding rate measured by the external institution was higher than that of conventional materials.
[0085] <Example of method for impregnating molten aluminum into a preform> [Example 1] 450g of B4C powder #800 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 16μm was mixed for 30 minutes in a V-type mixer. 5g of ethyl silicate was added to the mixed powder as a liquid binder, and the whole was placed in a Henschel mixer that applies shear force to the powder and stirred at high speed for 15 minutes to mix uniformly. The resulting mixed powder was placed in a 100mm x 100mm mold, covered with a lid, and pressurized at 160kgf / cm. 2 The molded body was placed in a sintering furnace, heated to 400°C at a heating rate of 50°C / hour, then held at 400°C for 3 hours for sintering, and then naturally cooled. The obtained sintered body (preform) had a shape of 100mm x 100mm x 35mm and weighed 449g. Calculated from the true specific gravity of boron carbide (B4C) of 2.51, this preform had a bulk specific gravity of 1.31, a filling rate (Vf) of boron carbide of 52%, and a void of 48%. This preform was heated at a heating rate of 100°C / hour, held at 500°C, and waited in a heated state for the next aluminum impregnation by high-pressure pressing.
[0086] A die with an inner diameter of 300φ installed in a high-pressure press was heated to about 250°C by a burner. Then, the preform that had been kept in a heated state was placed in the die of the press, and molten aluminum melted at 800°C was poured into the die, and high-pressure casting was performed as described below. As shown in Figs. 1A and 1B, after molten aluminum 1 melted at 800°C was poured into the die containing the preform 2, the upper punch 5 of the press 10 was immediately lowered, and a load was applied to the upper punch 5 so that the pressure of the molten aluminum 1 became 70 MPa. As described above, since the inner diameter of the die was 300φ, the load of the press 10 was about 500 t.
[0087] After the load was applied and maintained for 5 minutes, the upper punch 5 was removed, and the lower punch 4 was immediately pushed up to lift the impregnated body (composite) 3 to the upper side of the press (see FIG. 1C), and the composite was allowed to cool naturally. After the composite was cooled to a level where it could be handled, the solidified aluminum surrounding the composite 3 was removed by machining, and the composite 3 was taken out.
[0088] The specific gravity of the extracted composite was measured to be 2.61. This value was almost identical to the calculated value for when the voids in the preform were completely impregnated with aluminum, so it was concluded that the material extracted above was a dense composite of B4C and aluminum. The high content (volume filling rate) of light boron carbide, which has a specific gravity of 2.52, of 52v%, made it possible to produce a lightweight composite with a specific gravity of 2.61. In addition, when a portion of the obtained composite was cut out and the surface was subjected to X-ray diffraction measurement, the generation of Al4C3 due to the decomposition of B4C could not be confirmed.
[0089] The above-obtained B4C material with a volume filling rate (Vf) of 52v% and a thickness of 35mm was subjected to a measurement of its radiation shielding effect by an external measurement agency. As a result, the shielding effect against neutrons from the isotope of Cf252 was 61%, which was a high value. In addition, a bending test was performed on the composite of this example based on JIS-R1061, and the strength was 183Mpa, which was high. These facts indicate that the composite obtained in this example is a useful material that effectively combines the properties of the B4C powder, which is lightweight and has excellent radiation shielding effect, and is used as a raw material and is combined without decomposition.
[0090] [Example 2] 230 g of B4C powder #180 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 70 μm and 260 g of B4C powder #800 with an average particle size of 16 μm similar to that used in Example 1 were mixed for 30 minutes in a V-type mixer. 15 g of ethyl silicate was added to the mixed powder as a liquid binder, and mixed for 15 minutes in a Henschel mixer as in Example 1.
[0091] The obtained mixed raw material was press molded and sintered in the same manner as in Example 1 to produce a preform having a shape of 100 mm x 100 mm x 26 mm, a bulk density of 1.66, a B4C filling rate Vf of 66%, and a porosity of 34 v%. The obtained preform was placed in a mold of a high-pressure press in the same manner as in Example 1 and high-pressure impregnated with molten aluminum. Thereafter, it was naturally cooled in the same manner as in Example 1, and the solidified aluminum around the composite was removed.
[0092] The specific gravity of this composite was 2.57, which was almost the same as the calculated value when aluminum was impregnated into the voids of the preform, and it was a dense composite made of B4C and aluminum. In addition, X-ray diffraction was performed on the surface of the composite in the same manner as in Example 1. As a result, as in Example 1, the generation of Al4C3 and the like could not be observed. As described above, by combining B4C powders with different average particle sizes and using them as raw materials, a composite with a B4C powder filling rate of 66v% higher than that in Example 1 could be produced. In addition, a light composite with a specific gravity of 2.57 could be produced despite the high B4C filling rate.
[0093] The above-obtained B4C material with a volume filling rate (Vf) of 66v% and a thickness of 26 mm was subjected to a measurement of its radiation shielding effect by an external measurement agency. As a result, the shielding effect against neutrons from the isotope Cf252 of Californium (Cf) was 31%, which was a high value. In addition, a bending test was performed on the composite of this example based on JIS-R1061, and the strength was 193 MPa, which was high. These facts indicate that the composite obtained in this example is a useful material that effectively combines the properties of the B4C powder, which is lightweight and has excellent radiation shielding effect, and is used as a raw material and is composited in its original state without decomposition.
[0094] [Example 3] 820 g of A-200 (trade name, manufactured by Takehara Chemical Industry Co., Ltd.), which is a barium sulfate (BaSO4) powder with an average particle size of 15 μm, was mixed uniformly in the same manner as in Example 1. As a liquid binder, a silicone-based resin solution was used, which was prepared by dissolving soluble silicone resin KR-200 (manufactured by Shin-Etsu Chemical Co., Ltd.) in ethanol to a concentration of 20 w% by mass. Then, 50 g of the prepared silicone-based resin solution was added to the mixed BaSO4 powder, and high-speed stirring was performed using a Henschel mixer in the same manner as in Example 1.
[0095] The preform produced by the same method and procedure as in Example 1 had a size of 100 mm x 100 mm x 28 mm, a bulk specific gravity of 2.92, and a filling rate of BaSO4 of 65v%. Next, in the same manner as in Example 1, the preform was impregnated with molten aluminum at high pressure and processed to extract a composite. The specific gravity of the composite was 3.86, which was almost the same as the calculated value (theoretical value), and it was confirmed that it was a dense composite made of BaSO4 and aluminum.
[0096] The above-obtained material with a volume filling rate (Vf) of 65v% and a thickness of 28mm was subjected to a test for radiation shielding effect at an external measuring agency. As a result, the projection rate of cesium (Cs) gamma rays Cs137 was 35%, and the shielding rate of X-rays 150Kv was 99.5%, which were high values. In addition, a bending test was performed on the composite of this example based on JIS-R1061, and the strength was 193Mpa, which was high. These facts show that the composite obtained in this example is a useful material that effectively combines the properties of BaSO4 powder, which is lightweight and has excellent radiation shielding effect, and is used as a raw material and is combined in its original state without decomposition.
[0097] [Example 4] 250 g of B4C powder #800 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 16 μm and 270 g of WA-100 (manufactured by Yamaishi Metals Co., Ltd.), an aluminum powder with an average particle size of 18 μm, were used as raw material powders and uniformly mixed in the same manner as in Example 1. 10 g of liquid ethyl silicate (manufactured by Colcoat Co., Ltd.) was added as a binder to this, and high-speed stirring was performed using a Henschel mixer in the same manner as in Example 1.
[0098] The preform produced by the same method and procedure as in Example 1 had a shape of 100 mm x 100 mm x 33 mm, a bulk specific gravity of 1.30, and a total filling rate of B4C powder and aluminum powder (Al powder) of 50v%. Next, the preform was infiltrated with molten aluminum at high pressure and processed in the same manner as in Example 1, and a composite was taken out. The specific gravity of the composite in this example was 2.65, which was almost the same as the calculated value when all the voids in the preform were infiltrated with molten aluminum.
[0099] The volume ratio of the two types of raw material powder, B4C powder and Al powder, is approximately 1:1, so that about 50v% of the preform is aluminum powder. Therefore, the amount of aluminum in the obtained composite is 75v% in total, including the aluminum impregnated in the preform, so that the composite is composed of 75v% aluminum powder and the remaining 25v% B4C powder. From the above, it was confirmed that it is possible to control the concentration of the radiation shielding powder by mixing an appropriate amount of aluminum powder into the raw material of the preform. Moreover, in the above case, by using B4C powder as the raw material of the preform, a light composite with a specific gravity of 2.65 could be manufactured. In addition, a bending test was performed on the composite of this embodiment based on JIS-R1061, and the result was a high strength of 182Mpa.
[0100] [Example 5] A raw material for the preform was prepared by adding 280 g of BaSO4 powder A-200 (trade name, manufactured by Takehara Chemical Industry Co., Ltd.) with an average particle size of 15 μm, 395 g of aluminum powder WA-100 (manufactured by Yamaishi Metals Co., Ltd.) with an average particle size of 18 μm, and 50 g of a 20 wt % solution of silicone resin KR-200 dissolved in ethanol, which was the same as that used in Example 3. The raw material was stirred at high speed with a Henschel mixer in the same manner as in Example 1.
[0101] Thereafter, a preform was produced by the same method and procedure as in Example 1, and had a size of 100 mm x 100 mm x 38 mm, a bulk density of 1.77, and a total filling rate (Vf) of the BaSO4 powder and the Al powder of 55v%.
[0102] Next, the preform obtained above was infiltrated with molten aluminum at high pressure in the same manner as in Example 1, and processed to extract a composite. The specific gravity of the prepared composite was 2.99, which was almost the same as the calculated value of the dense body. In the composite of this example, 70v% of the preform was aluminum powder, so that the total of the aluminum in the composite including the impregnated aluminum was 84v%, and the remaining 16v% was BaSO4 powder. Thus, the composite of this example, like the composite of Example 4, is an example in which it is possible to control the concentration of barium sulfate powder, which is a radiation shielding powder in the composite, by mixing aluminum powder into the raw material of the preform. In addition, the composite of this example was subjected to a bending test based on JIS-R1061, and the result was a high strength of 212Mpa.
[0103] [Example 6] 270 g of B4C powder #800 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 16 μm and 495 g of A-200 (trade name, manufactured by Takehara Chemical Industry Co., Ltd.), which is BaSO4 powder with an average particle size of 15 μm, were used as raw material powders and uniformly mixed in the same manner as in Example 1. 15 g of liquid ethyl silicate (manufactured by Colcoat Co., Ltd.) was added as a binder to this, and high-speed stirring was performed using a Henschel mixer in the same manner as in Example 1.
[0104] Thereafter, a preform was produced by the same method and procedure as in Example 1, and had a size of 100 mm x 100 mm x 38 mm, a bulk density of 2.00, and a total filling rate (Vf) of the B4C and BaSO4 powders of 57v%.
[0105] Next, the composite was extracted by impregnating the composite with molten aluminum in the same manner as in Example 1. The specific gravity of the prepared composite was 3.16, which was almost the same as the calculated value when the preform was impregnated with molten aluminum. The obtained composite had 28.5v% B4C, 28.5v% BaSO4, and 43v% aluminum. As shown in this example, it was confirmed that a composite containing two types of radiation shielding powders can be manufactured by the manufacturing method of the present invention. In addition, a bending test was performed on the composite of this example based on JIS-R1061, and the result was a high strength of 199Mpa.
[0106] [Example 7] 380g of B4C powder #800 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 16μm and 1270g of tungsten metal powder W-4 (manufactured by Nippon Shinkinzoku Co., Ltd.) with an average particle size of 3μm were used and uniformly mixed in the same manner as in Example 1. At that time, water glass No. 4 (manufactured by Fuji Chemical Co., Ltd.) was diluted with water and used as a binder, and an amount equivalent to 16g in terms of SiO2 was added and stirred at high speed with a Henschel mixer in the same manner as in Example 1. Then, a preform was produced by the same method and procedure as in Example 1. The preform had a shape of 100mm x 100mm x 32mm, its bulk specific gravity was 5.18, and the total filling rate (Vf) of B4C and tungsten W was 68%.
[0107] Next, the composite was high-pressure impregnated with molten aluminum in the same manner as in Example 1, processed, and extracted. The specific gravity of the composite was 6.04, which was almost the same as the calculated value when the preform was impregnated with molten aluminum. The composite obtained was a composite with 48.5v% B4C, 20.4v% tungsten, and 32v% aluminum. In addition, a bending test was performed on the composite of this example based on JIS-R1061, and the result was a high strength of 192Mpa.
[0108] As shown in this example, a composite containing two types of radiation shielding powders could be produced by the method of the present invention, as in Example 6. In addition, the composite in this example contains 20.4v% tungsten, and has a specific gravity of 6.04, which is considerably lighter than the specific gravity of 19.5 of pure tungsten.
[0109] [Example 8] Using B4C powder #800 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 16 μm, the same as in Example 1, ethyl silicate binder was added, mixed, molded, and fired in the same manner to create a preform with dimensions of 100 mm x 100 mm x 35 mm, the same bulk density of 1.31, a boron carbide filling rate (Vf) of 52%, and voids of 48 v%. The preform was heated and left on standby at a temperature of 400°C.
[0110] The preform was placed in a mold with an inner diameter of 300 mm and heated to 250°C in the same manner as in Example 1, and a low melting point alloy (zinc alloy: ZDC2, specific gravity 6.8) melted at 500°C was cast, and high pressure impregnated at 70 MPa (500 t as press load). After holding for 10 minutes, it was immediately cooled, cooled to room temperature, and the composite was removed. The specific gravity of the composite was 4.18, and it was a composite material impregnated with almost 100% low melting point zinc alloy. There was no decomposition reaction due to the generation of B4C. Furthermore, a bending test was performed on the composite of this example based on JIS-R1061, and the strength was high at 223 MPa.
[0111] [Comparative Examples 1 and 2] The same B4C powder as used in Example 1 was used and mixed, and 2g of fine silica powder (manufactured by Yamamori Tsuchimoto Seisakusho Co., Ltd.) with an average particle size of 1.2 μm and 3g of water were added to 450g of this (net volume 182ml), and the mixture was inserted into a mold in the same manner as in Example 1, press-molded, and the molded bodies were fired at different temperatures of 400°C and 800°C, respectively, and cooled. The obtained molded bodies did not have the strength of a preform in either firing temperature, could not be handled, and could not be subjected to high-pressure impregnation of molten aluminum.
[0112] [Comparative Examples 3 and 4] The same B4C powder as used in Example 1 was used and mixed, and 4 g of fine silica powder of LeoSeal QS-9 (manufactured by Tokuyama Corp.) with an average particle size of 22 nm (22 mμ) and 64 g of water were added to 450 g (net volume 182 ml) of this, and the mixed powder prepared in the same manner as in Example 1 was inserted into a mold and press-molded. The molded bodies obtained by press molding were fired at different temperatures of 400°C or 800°C, respectively, and cooled. The molded bodies after firing did not have the strength of a preform in either case of firing temperature, could not be handled, and could not be subjected to high-pressure impregnation of molten aluminum.
[0113] [Comparative Example 5] A B4C preform was prepared in the same manner as in Example 1, and the obtained preform was placed in a mold and cast at 900°C using molten aluminum in the same manner as in Example 1. In this comparative example, the temperature was then held at 900°C for 20 minutes, and a composite was prepared in the same manner as in Example 1. When the surface of the composite was processed, it was found to be blackened, so a part of it was cut out and examined by X-ray diffraction. As a result, in addition to the main raw material B4C, small peaks of Al4C3 were observed at 2θ = 31.8 °, 35.8 °, 40.1 °, and 55 °. From this, it was confirmed that in the case of the composite of this comparative example, if it is kept at a high temperature in the press mold for a long time, the raw material B4C of the preform will be partially decomposed, and the composite will not be in a good condition.
[0114] [Comparative Example 6] 890 g of A-200 (trade name, Takehara Chemical Industry Co., Ltd.), a BaSO4 powder with an average particle size of 15 μm, similar to that used in Example 5, was mixed uniformly in the same manner as in Example 1. Then, 50 g of a 20 wt % solution of silicone resin KR-200 in ethanol, similar to that used in Example 3, was added, and high-speed stirring was performed with a Henschel mixer in the same manner as in Example 1.
[0115] The preform produced by the same method and procedure as in Example 1 had a shape of 100 mm x 100 mm x 33 mm, and the filling rate of BaSO4 was 60v%. Next, it was set in a mold by the same method as in Example 1, impregnated with molten aluminum at 950 ° C, processed, and the composite was taken out. When the surface was processed and observed visually, there were many pores. The reason for this is thought to be that BaSO4 decomposed into BaO and SO2 when heated at high temperatures.
[0116] Table 1 shows the preparation conditions of the preforms in Examples 1 to 8 and Comparative Examples 1 to 6, and the properties and evaluations of the obtained composites in Examples 1 to 8 and Comparative Examples 5 and 6. In Table 1, "Yes" and "No" of decomposition indicate whether decomposition was observed in the radiation-shielding powder constituting each composite.
[0117] TIFF0007606793000003.tif197170
[0118] <Example of method for impregnating preform with organic / inorganic sealant> Next, the method of producing a radiation shielding composite by impregnating a special liquid organic inorganic sealing agent into the voids of a porous molded body (preform) according to the second production method of the present invention will be described with reference to examples and comparative examples. The reason why the bending test is performed on the composites in the following examples is as follows. When the voids of the preform are impregnated with a liquid organic inorganic sealing agent, components derived from the organic inorganic sealing agent remain in the voids of the preform. Here, in the case of a composite having a configuration in which the voids of the preform are impregnated with a liquid organic inorganic sealing agent, it is not necessary to impregnate all of the voids of the preform as in the case of impregnating with molten aluminum described above, and some voids may remain. According to the study by the present inventors, even in such a configuration, as long as the liquid organic inorganic sealing agent occupies 25% by volume or more of the voids of the preform before being impregnated with the liquid organic inorganic sealing agent, the composite obtained has sufficient strength and can be used as a building material such as a wall material or a ceiling material. In other words, if a bending test is performed on the obtained composite to confirm its strength, it can be confirmed that a sufficient amount of the solidified organic / inorganic sealing agent and / or the heat-treated organic / inorganic sealing agent remains in the voids of the preform. As shown below, the composites of the examples have sufficient strength and are of the configuration specified in the present invention.
[0119] [Example 9] A preform weighing 262 g and having dimensions of 100 mm x 100 mm x 20 mm was produced using 270 g of B4C powder #800 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 16 μm and the same material composition as in Example 1 described above, mixed, molded, fired, and cooled in the same manner. The obtained preform had a bulk density of 1.31 calculated from the true density of boron carbide (B4C) of 2.51, a filling rate (Vf) of boron carbide of 52 v%, and voids of 48 v%.
[0120] As the organic inorganic sealing agent, Permeate HS-200 (trade name, manufactured by D&D Co., Ltd., hereinafter simply referred to as Permeate) with a viscosity of 15.5 mPa·s, a specific gravity of 1.15, a siloxane bond, and a non-volatile content of 85 w% was used. Using a reduced pressure vessel 30 as shown in the schematic diagram of FIG. 2, the preform 32 was impregnated with the permeate, which is a liquid organic inorganic sealing agent 31, as described below. The preform 32 obtained above was placed in an interior vessel 34 placed in the reduced pressure vessel 30, and a weight (not shown) was placed on top to prevent it from floating. The permeate was then poured into the interior vessel 34 via an organic inorganic sealing agent pouring vessel 35 so that the entire preform was immersed in the permeate.
[0121] The entire reduced pressure vessel 30 was evacuated to a vacuum by a vacuum pump (not shown) through the pressure reduction port 36 and maintained for 10 minutes. After that, the vacuum was released to return the inside of the reduced pressure vessel 30 to normal pressure, and then air from a compressor (not shown) was reduced in pressure to 4 atmospheres by a pressure reduction device (not shown) and slowly introduced into the reduced pressure vessel 30 to pressurize the entire reduced pressure vessel to 4 atmospheres. This was maintained for 5 minutes to pressure-impregnate the permeate into the preform 32.
[0122] After that, the reduced pressure vessel 30 was returned to atmospheric pressure, and the preform 32 was removed from the indoor vessel 34 and left to stand overnight. The temperature was then raised at 50°C / hour, and heat-treated at 400°C for 3 hours to produce a composite with radiation shielding properties. The specific gravity of this material (composite) was measured, and the composite was found to be 52v% B4C, 30v% organic / inorganic sealing agent (62.5v% of the voids in the preform), and 18v% voids. The specific gravity of the obtained material (composite) is summarized in Table 2.
[0123] The material (composite) obtained above, with a volume filling rate (Vf) of 52v% of B4C powder and a thickness of 20mm, was subjected to measurement of its radiation shielding effect by an external measurement agency. The shielding rate of the neutron radiation Cf252 of the isotope of Cf was measured, and the shielding rate was 30%, which was a high value. There is no other shielding material that has such a neutron radiation shielding rate with a thickness of 20mm. This result shows that the composite obtained in this example is a useful material that effectively combines the properties of B4C powder, since the B4C powder used as the raw material, which is lightweight and has excellent radiation shielding effect, is composited as it is without decomposition. Meanwhile, a test piece for measuring bending strength of 3mm x 4mm x 40mm was prepared from the composite obtained above, and a bending test was performed based on JIS-R1061. As a result, a strength of 25Mpa was obtained. This value is about 5 to 10 times that of gypsum board and concrete plate measured using the same method, confirming that the material is suitable for use as an exterior wall material and radiation storage container.
[0124] [Example 10] Using 230 g of B4C powder #180 (manufactured by Dojin Sangyo Co., Ltd.) with an average particle size of 70 μm and 100 g of B4C powder #800 with an average particle size of 16 μm, a molded body of 100 mm × 100 mm × 20 mm was produced in the same manner as in Example 2. This molded body was fired at 400 ° C. in the same manner as in Example 1, and a preform with a weight of 235 g and a bulk density of 1.66 was obtained. The obtained preform had a B4C volume filling rate (Vf) of about 66 v % and a void of 32 v %. Using this obtained preform, the permeate was vacuum-impregnated in the same manner as in Example 8 and heat-treated at 400 ° C., a radiation shielding material with 66 v % B4C, 19 v % permeate (organic inorganic sealing agent), and 15% void was obtained.
[0125] The material (composite) of the B4C powder obtained above, with a volume filling rate (Vf) of 66v% and a thickness of 20 mm, was subjected to measurement of its radiation shielding effect by an external measurement agency. The shielding rate of the neutron radiation of the isotope Cf252 of Californium (Cf) was measured, and the shielding rate was 34%, which was a high value. In addition, a bending test piece was prepared in the same manner as in Example 8, and the bending strength was measured, which showed a high value of 41 MPa.
[0126] [Example 11] In the same composition as in Example 3, 240 g of A-200 (trade name, manufactured by Takehara Chemical Industry Co., Ltd.), which is a barium sulfate (BaSO4) powder with an average particle size of 15 μm, was used and mixed uniformly in the same manner as in Example 1. As a binder, a silicone-based resin solution was used in which a soluble silicone resin KR-200 (manufactured by Shin-Etsu Chemical Co., Ltd.) was dissolved in ethanol and prepared to a concentration of 20 w% by mass. Then, 15 g of the prepared silicone-based resin solution was added to the mixed BaSO4 powder, and mixed powder was obtained by high-speed stirring with a Henschel mixer in the same manner as in Example 1.
[0127] The mixed powder obtained above is placed in a 60 mm diameter mold and pressurized at 160 kg / cm 2 This was then heated at 400°C in the same manner as in Example 1 to produce a preform in the shape of a disk of 60 mmφ×27.8 mm thickness and weighing 235 g. The bulk density of the resulting preform was 2.95, with BaSO4 at 65v% and voids at 35v%.
[0128] Next, a composite was obtained as follows, using a liquid organic inorganic sealing agent on the preform obtained above. As a liquid organic inorganic sealing agent, ethyl silicate oligomer manufactured by Colcoat Co., Ltd., containing 40 wt% in terms of SiO2, was placed in a container, and the preform obtained above was immersed in it, and the preform was impregnated with ethyl silicate by vacuum and pressure of 4 atmospheres. Then, the impregnated body impregnated with the liquid organic inorganic sealing agent was taken out of the container, left in the air for 48 hours, and heat-treated at 400°C for 3 hours, to obtain a composite having a radiation shielding function, in which BaSO4 was 65v%, the non-volatile content of SiO2 generated from ethyl silicate was 10v% (28.6v% of the voids in the preform), and the remainder was 23v%.
[0129] The material (composite) obtained above, with a volume filling rate (Vf) of 65v% and a thickness of 27.8mm, was subjected to measurement of the radiation shielding effect by an external measurement agency. As a result, the projection rate of cesium (Cs) gamma rays Cs137 was 36%, and the shielding rate of X-rays 150Kv was 99.7%, which were high values. In addition, a bending test piece was prepared in the same manner as in Example 1, and the bending strength was measured, showing a high value of 28Mpa, confirming that the material is fully usable as a structure.
[0130] [Example 12] 54g of B4C powder with an average particle size of 16μm, 110g of A-200 (trade name) BaSO4 powder with an average particle size of 15μm, and 7g of ethyl silicate as a liquid binder were added, and the raw materials were mixed and press molded in the same manner as in Example 1, and then fired at 400℃ to obtain a preform weighing 165g, measuring 60mmφ×30mm, and having a bulk density of 1.93. The obtained preform was 29v% B4C, 29v% BaSO4, and 42v% voids.
[0131] Using a reduced pressure vessel 30 as shown in Fig. 2 and liquid ethyl silicate as an organic / inorganic sealing agent 31, the preform 32 obtained above was immersed in the ethyl silicate liquid, vacuum impregnated, and then heat-treated at 400°C in the same manner as in Example 8 to obtain a composite with radiation shielding properties. The obtained composite had 29v% B4C, 29v% BaSO4, 17v% non-volatile content of SiO2 of the ethyl silicate (40.4v% of the voids in the preform), and 25v% voids.
[0132] The material (composite) containing the B4C powder, BaSO4 powder, and liquid organic-inorganic sealing agent obtained above was subjected to measurement of radiation shielding effect by an external measurement agency. As a result, the projection rate of cesium (Cs) gamma rays Cs137 was 25%, and the shielding rate of X-rays 150Kv was 98%, which were high values. In addition, bending test pieces were prepared in the same manner as in the other examples, and the bending strength was measured, showing a high value of 32Mpa, confirming that the material is sufficiently usable industrially as a structure.
[0133] Table 2 shows the embodiments of the specific powders constituting the preforms used to form the composites of Examples 9 to 12, the amounts of organic / inorganic sealing agents in the voids of the preforms and in the composites, and the radiation shielding effects. TIFF0007606793000004.tif88170
[0134] [Comparative Examples 7 to 10] Using each preform that was used in preparing the composites of Examples 9 to 12 having the configurations shown in Table 2, but was not impregnated with a liquid organic / inorganic sealing agent, test pieces were prepared and bending strength was measured in the same manner as in the Examples. The measurement results obtained are summarized in Table 3. For comparison, the bending strength magnification of each composite of Examples 9 to 12 is shown in parentheses. As shown in Table 3, it was confirmed that the bending strength of the composites of the Examples in which the organic / inorganic sealing agent was compounded with the preform could be significantly improved compared to the materials of the Comparative Examples.
[0135] TIFF0007606793000005.tif43170
[0136] [Comparative Example 11] A preform having a bulk density of 1.31, a B4C filling rate (Vf) of 52v%, and a void of 48v%, similar to that prepared in Example 9, was used, and composited with an organic inorganic sealant as described below to obtain a composite of Comparative Example 11. Permeate HS-200, which has a viscosity of 15.5mPa·s, a specific gravity of 1.15, a siloxane bond, and a non-volatile content of 85w%, similar to that used in Example 9, was used as a liquid organic inorganic sealant, and this was diluted with ethanol to adjust the non-volatile content to 20w%. Then, after impregnating with a liquid organic inorganic sealant in the same manner as in Example 9, a composite material was obtained by heat treatment. From the results of weight measurement, the material was 52v% B4C, 8v% organic inorganic sealant (16.0v% of the voids in the preform), and 36v% voids. The bending strength of this material was measured in the same manner as in the examples, and the bending strength was 11 MPa, which was not high. The reason for this is thought to be due to the low amount of organic-inorganic composite agent in the voids of the preform.
[0137] [Comparative Example 12] A preform having a bulk density of 2.95, a filling rate (Vf) of BaSO4 of 65v%, and a void of 35v% was used as prepared in Example 11, and the composite of Comparative Example 12 was obtained by compounding with an organic inorganic sealant as described below. As a liquid organic inorganic sealant, the liquid ethyl silicate oligomer solution used in Example 11 was diluted with water to adjust the non-volatile content of SiO2 to a 10w% solution. Then, the preform was impregnated with the liquid organic inorganic sealant in the same manner as in Example 11, and then the material was heat-treated to obtain a composite material. From the results of weight measurement, the material was 65v% BaSO4, 4v% non-volatile content of SiO2 generated from ethyl silicate (11v% of the voids in the preform), and 31v% of the voids. When the bending strength of this material was measured in the same manner as in the example, the bending strength was 9MPa, which was low.
[0138] [Comparative Example 13] A preform having a bulk density of 1.31, a B4C filling rate (Vf) of 52v%, and a void of 48v%, similar to that prepared in Example 9, was used, and composited with an organic / inorganic sealant as described below to obtain a composite of Comparative Example 13. As a liquid organic / inorganic sealant, a silicone resin KR220l (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.) solution having a viscosity of 150mPa.m dissolved in ethanol with a non-volatile content of 40w% was used. The silicone resin solution was impregnated into a preform in the same manner as in Example 9, and a composite material was obtained by heat treatment. The obtained material had a B4C Vf of 52v%, a non-volatile content of SiO2 generated from the silicone resin of 3v% (6.2v% of the voids in the preform), and a void of 45v%. The bending strength of this material was also measured in the same manner as in the example, and the bending strength was 6MPa, which was low. The reason for this is believed to be that the silicone resin solution, which has a high viscosity, did not sufficiently impregnate the preform, and the amount of the organic / inorganic sealant impregnated was low.
[0139] TIFF0007606793000006.tif59170 [Explanation of symbols]
[0140] 1: Molten aluminum 2: Preform 3: Composite impregnated with molten aluminum 4: Lower punch 5: Upper punch 10: Press mold 30: Reduced pressure vessel 31: Organic / inorganic sealants 32: Preform 33: Opening and closing fixture for reduced pressure vessel 34: Indoor container 35: Organic / inorganic sealant container 36: Pressure reduction port 37: Pressure port 38: Pressure gauge
Claims
1. A composite having a radiation-shielding function, comprising a powder having a radiation-shielding effect, the powder being composited together in a total amount within a range of 3 volume % or more and 85 volume % or less, A porous composition which is a molded and fired product made of a mixture containing one or more types of powder having a radiation shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron powder, boron oxide powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide, and a silica-based binder that is not in powder form. The voids in the molded body (preform) are all impregnated and filled with at least one of a molten low-melting point metal selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin and lead, which has a melting point of 200°C or more and 900°C or less, and then solidified to form a composite, or at least 25 volume % or more of the voids in the porous molded body (preform) are impregnated with a liquid organic / inorganic sealing agent, which is then solidified to form a composite, and The composite having a radiation-shielding function is characterized in that the non-powdered silica-based binder is at least one selected from the group consisting of a liquid silicone resin, a silicone resin solution obtained by dissolving a silicone resin in an organic solvent, and a silica alkoxide made of silica and an organic substance and cured by heating at a temperature of 900°C or less, and has a property of being able to form a porous molded body (preform) that is the molded and fired product at a temperature at which the radiation-shielding powder is not decomposed.
2. The mixture is a mixture of 100 parts by mass of the radiation shielding powder and the liquid silica-based binder in an amount of SiO 2 2. The composite having a radiation-shielding function according to claim 1, wherein 0.5 to 10 parts by mass of the compound is added in terms of conversion.
3. 2. The composite having a radiation-shielding function according to claim 1, wherein the liquid organic / inorganic pore-sealing agent is present in pores of the porous molded body (preform) as a solidified product of the organic / inorganic pore-sealing agent and / or a heat-treated product of the organic / inorganic pore-sealing agent, the solidified product of the organic / inorganic pore-sealing agent and / or the heat-treated product of the organic / inorganic pore-sealing agent occupying 25% by volume or more of 100% by volume of the pores of the porous molded body (preform) before impregnation, and when the entire preform after impregnation is taken as 100% by volume, the solidified product of the organic / inorganic pore-sealing agent and / or the heat-treated product of the organic / inorganic pore-sealing agent occupy 5% by volume or more.
4. The liquid organic / inorganic sealing agent has a low viscosity of 50 mPa·s or less and contains 30 mass% or more of non-volatile components. Methyl silicate Si(OCH 3 ) 4 or a liquid methyl silicate compound in which the methyl silicate is partially hydrolyzed to form a dimer or tetramer oligomer, and the non-volatile component content is adjusted to 30 mass % or more; Ethyl silicate Si(OC 2 H 5 ) 4 or a liquid ethyl silicate compound in which the ethyl silicate is partially hydrolyzed to form a dimer or tetramer oligomer, and the non-volatile component content is adjusted to 30 mass % or more; A silicone resin or a derivative thereof having a siloxane bond and adjusted so that the non-volatile component content is 30% by mass or more; 4. The composite having a radiation-shielding function according to claim 1 or 3, which is at least any one selected from the group consisting of liquid alkoxysilane compounds which are alkoxysilane derivatives and react with moisture in the air to undergo a condensation reaction to produce a silicone-oxygen organic compound (Si-O-R).
5. A method for producing a composite having a radiation-shielding function, comprising using at least one of a molten low-melting-point metal selected from the group consisting of aluminum metal, an aluminum alloy, zinc, tin, and lead, or a low-melting-point alloy of said low-melting-point metal and another metal as a matrix, and containing a powder having a radiation-shielding effect in a total amount within a range of 3 volume % or more and 85 volume % or less, comprising: a step of adding a non-powdered silica-based binder to one or more of the powders having a radiation shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron oxide powder, boron powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide, and then molding the mixture, and firing the obtained molded body at a temperature of 300° C. or higher and 900° C. or lower to produce a porous molded body (preform); the non-powdered silica-based binder used in the step is at least one liquid silica-based binder selected from the group consisting of a liquid silicone resin, a silicone resin solution obtained by dissolving a silicone resin in an organic solvent, and a silica alkoxide made of silica and an organic substance and heated and cured at a temperature of 900° C. or lower; and a step of casting a molten metal of at least one of a low-melting-point metal selected from the group consisting of aluminum metal, aluminum alloy, zinc, tin and lead, which has a melting point of 200°C to 900°C, into the porous molded body (preform) obtained in the step, holding the molten metal at a high pressure of 20 MPa to 200 MPa for 3 to 15 minutes in order to impregnate the porous molded body (preform) with the molten metal, and then removing the composite impregnated with the molten metal within 15 minutes and cooling it, thereby suppressing decomposition of the radiation-shielding powder in the composite.
6. A method for producing a composite having a radiation-shielding function, comprising preparing a composite containing a powder having a radiation-shielding effect in a total amount of 3 volume % or more and 85 volume % or less, the powder being composited, the method comprising the steps of: a step of adding a non-powdered silica-based binder to one or more types of powder having a radiation shielding effect selected from the group consisting of gadolinium oxide powder, boron carbide powder, boron oxide powder, boron powder, barium sulfate powder, strontium oxide powder, tungsten powder, tungsten oxide powder, tungsten carbide powder, molybdenum powder, molybdenum oxide powder, iron powder, iron oxide powder, and ferrite powder mainly composed of iron oxide, to form a mixture, and then firing the obtained molded body at a temperature of 300° C. or more and 900° C. or less to prepare a porous molded body (preform); and a compounding step of: impregnating voids of the porous molded body (preform) obtained in the step of producing the porous molded body (preform) with a liquid organic / inorganic sealing agent containing 30% by mass or more of non-volatile components and having a viscosity of 50 mPa s or less, or impregnating the voids at a pressure of 10 atmospheres or less by pressurizing the liquid organic / inorganic sealing agent after vacuum impregnation, and then heating the liquid organic / inorganic sealing agent to a temperature of 200° C. or more and 900° C. or less, so that a solidified product of the liquid organic / inorganic sealing agent and / or a heat-treated product of the liquid organic / inorganic sealing agent remains in an amount of 25% by volume or more relative to 100% by volume of the voids of the porous molded body (preform), thereby compounding the radiation-shielding powder with a component derived from the liquid organic / inorganic sealing agent.
7. The liquid organic / inorganic sealing agent has a low viscosity of 50 mPa·s or less and contains 30 mass% or more of non-volatile components. Methyl silicate Si(OCH 3 ) 4 or a liquid methyl silicate compound in which the methyl silicate is partially hydrolyzed to form a dimer or tetramer oligomer, and the non-volatile component content is adjusted to 30 mass % or more; Ethyl silicate Si(OC 2 H 5 ) 4 or a liquid ethyl silicate compound in which the ethyl silicate is partially hydrolyzed to form a dimer or tetramer oligomer, and the non-volatile component content is adjusted to 30 mass % or more; A silicone resin or a derivative thereof having a siloxane bond and adjusted so that the non-volatile component content is 30% by mass or more; 7. The method for producing a composite having a radiation-shielding function according to claim 6, wherein the alkoxysilane derivative is at least any one selected from the group consisting of liquid alkoxysilane compounds which react with moisture in the air to undergo a condensation reaction to produce a silicone-oxygen-organic compound (Si-O-R).
8. The mixture is a mixture of 100 parts by mass of the radiation shielding powder and the liquid silica-based binder in an amount of SiO 2 The method for producing a composite having a radiation-shielding function according to claim 5 or 6, wherein 0.5 to 10 parts by mass of the compound is added in terms of conversion.
9. Furthermore, in the step of producing the porous molded body (preform), when aluminum powder, aluminum alloy powder, or ceramic powder is added to the radiation-shielding powder and the total amount of the aluminum metal powder, aluminum alloy powder, or ceramic powder and the radiation-shielding powder is taken as 100 mass %, the non-powdered silica-based binder is SiO 2 6. The method for producing a composite having a radiation-shielding function according to claim 5, wherein the porous molded body (preform) is produced by adding 0.5 to 10 mass % of the compound in terms of the converted amount.
Citation Information
Patent Citations
Composite material and preparation thereof
JP1985096746A
Cask and its material
JP1998319183A
Aluminum alloy material, its production method and basket and cask using the same
JP2002020828A
Aluminium-base complex material, production method therefor and complex product therewith
JP2003121590A
Aluminum-ceramic composite and its producing method
JP2004323291A
